Zakaj latinica ni dovolj - Hmeljak Sangawa, Kristina (Knjižnica, 2020)
Purpose: The problem of information loss inherent in the romanisation of Chinese, Japanese and Korean names is examined together with the problems it poses both to librarians who record book information and to library users who search for resources written in East Asian languages in a catalogue containing only romanised transcriptions.Methodology/approach: Firstly, we describe the writing systems used to write Chinese, Korean and Japanese, the romanisation standards for these languages, and the institutions providing authority data in Latin script. We then analyse the procedures for romanising East Asian proper names and then retrieving their original written form, and identify cases of information loss and irreversible transformations. As a case study, we present the difficulties encountered by librarians and users in the Library of the Department of Asian Studies of the Faculty of Arts at the University of Ljubljana (part of the Central Humanities Library and as such using the COBISS system) when using only romanised data to organise and search for library holdings in East Asian languages.Results: Information loss occurs in all methods of romanisation of Chinese, Korean and Japanese proper names presented in the previous sections. In the case of the Library of the Department of Asian Studies, this is a burden to both librarians and library users. Research limitations: We analysed the problem of the irreversibility of East Asian script romanisation in theory and in a case study involving one library; a more detailed analysis of other cases of Latin script catalogues hindering the management and use of library holdings in non-Latin scripts could be the object of future research.Originality/practical implications: This is the first analysis of the problem of information loss in romanised catalogues of East Asian library holdings in Slovenia, with a proposal for a possible solution using the Unicode standard.
Keywords: japonska pisava; kitajska pisava; knjižnični katalogi; korejska pisava; latinizacija